1991
DOI: 10.1016/0003-4975(91)90456-z
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic asphyxia

Abstract: During a 5-year period, we treated 14 cases of traumatic asphyxia. There were 12 male and 2 female patients ranging in age from 2 to 32 years. Most suffered crushing injuries at work or were run over by motor vehicles. Mild to severe cervicofacial cyanosis and petechiae developed in all patients. A fear response was reported by 12 of the patients. Subconjunctival hemorrhage was also found in 12 patients. Nine patients had tachypnea and 7 complained of dyspnea. Most of the patients suffered some associated inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…While survivors may manifest some neurological impairment including persistent loss of consciousness, prolonged confusion and visual disturbances including blindness, imaging studies of their brains have not shown specific deficits [10,17,18]. Similarly neuropathological evaluation of deceased victims does not demonstrate any definitive features.…”
Section: Discussionmentioning
confidence: 93%
“…While survivors may manifest some neurological impairment including persistent loss of consciousness, prolonged confusion and visual disturbances including blindness, imaging studies of their brains have not shown specific deficits [10,17,18]. Similarly neuropathological evaluation of deceased victims does not demonstrate any definitive features.…”
Section: Discussionmentioning
confidence: 93%
“…However, in these cases, there is often pathologic evidence of chest trauma (pulmonary contusion, rib fractures) or increased intrathoracic pressure affecting venous return and cardiovascular function (plethoric facies, edema, and ruptured small blood vessels above the shoulders). 24 In this study, we sought to determine if additional weight force on the back of an individual in the PMRP resulted in any evidence of respiratory compromise or risk for asphyxiation. Similar to previous studies, we found a restrictive pulmonary function pattern with PMRP but no significant further detriment in spirometric measures of FVC and FEV1 with the addition of 25 and 50 lbs of weight force on the back.…”
Section: Discussionmentioning
confidence: 99%
“…The second is vasomotor paralysis due to pressure on thoracic sympathetic nerves resulting in distension of vessels with desaturated blood. Additionally, reflex closure of glottis, which occurs to brace against the impending force as the victim has warning of being crushed [4,5], also augments the venous reflux. The venous reflux into cervico-facial region occurs through the competent venous valves of the internal jugular veins (IJVs), external jugular veins (EJVs) and vertebral veins (VVs).…”
Section: Discussionmentioning
confidence: 97%